2019
DOI: 10.1093/aobpla/plz037
|View full text |Cite
|
Sign up to set email alerts
|

How diverse can rare species be on the margins of genera distribution?

Abstract: Different genetic patterns have been demonstrated for narrowly distributed taxa, many of them linking rarity to evolutionary history. Quite a few species in young genera are endemics and have several populations that present low variability, sometimes attributed to geographical isolation or dispersion processes. Assessing the genetic diversity and structure of such species may be important for protecting them and understanding their diversification history. In this study, we used microsatellite markers and pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 81 publications
1
6
0
Order By: Relevance
“…The substantial increases in population size following divergence may be the result of the opening of new habitat or local adaptation following environmental change (see below for more discussion of local adaptation). Although additional genomic research of this genus is needed, our findings are consistent with the hypothesis that vicariance events and genetic isolation of local demes contributes to rapid diversification of Astragalus following climate change (Gavrilets & Vose, 2005; Simões et al., 2016), similar to diversification patterns in other rare and narrowly distributed plant species (e.g., Backes et al., 2019; Godt et al., 1996; Kropf et al., 2006).…”
Section: Discussionsupporting
confidence: 86%
“…The substantial increases in population size following divergence may be the result of the opening of new habitat or local adaptation following environmental change (see below for more discussion of local adaptation). Although additional genomic research of this genus is needed, our findings are consistent with the hypothesis that vicariance events and genetic isolation of local demes contributes to rapid diversification of Astragalus following climate change (Gavrilets & Vose, 2005; Simões et al., 2016), similar to diversification patterns in other rare and narrowly distributed plant species (e.g., Backes et al., 2019; Godt et al., 1996; Kropf et al., 2006).…”
Section: Discussionsupporting
confidence: 86%
“…This general observation corroborates the results of Torres-Florez et al ( 2017) in a review study on conservation genetics studies in Latin America, which found the use of SSRs in 33,1% of the articles. Solanaceae, with a series of studies of endemic and endangered Brazilian species without effective commercial use (LORENZ-LEMKE et al, 2006;FRANCESCHINELLI ET AL., 2013;BACKES et al, 2019;JOHN et al, 2019). Brummitt et al (2015) estimate that one out of every five plant species evaluated in the world is threatened with extinction.…”
Section: Resultsmentioning
confidence: 99%
“…This scenario proposes that species or their ancestors could have fragmented their distribution and isolated lineages, promoting allopatric speciation (Lorenz‐Lemke et al, 2010). In contrast, the colder and drier climate during the glacial periods would allow the expansion of grassland domains, such as Pampa and Chaco, leading grassland species to expand their distribution from the persistent populations (Backes et al, 2019; Latrubesse et al, 2012; Mäder & Freitas, 2019; Reck‐Kortmann et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Our results revealed that the P. parodii evolutionary history agrees with the proposal for ancient lineages (Avise, 2000). The ancestor of the Petunia genus has originated in the Pampa, and the Quaternary climate shifts strongly influenced its species distribution and diversification (Barros et al, 2015(Barros et al, , 2020Ramos-Fregonezi et al, 2015;Reck-Kortmann et al, 2014), with posterior migration to the north and higher elevations (Backes et al, 2019;Lorenz-Lemke et al, 2010).…”
Section: Functional Annotation Of Detected Outlier Snpsmentioning
confidence: 99%